Presumed insect sting–induced Takotsubo cardiomyopathy - Karl Maxemous, MD; Noah D.H. Lewis, MD, FRCPC, ABIM; Jason Chung, MD; Jumana Sarraj, MD, FRCPC; Samira Jeimy, MD, PhD, FRCPC (Journal of Allergy and Clinical Immunology: Global, 2025)
This report highlights a rare association between an insect sting and Takotsubo cardiomyopathy. It discusses the decisions surrounding the use and safety of epinephrine and a modified venom immunotherapy approach for desensitizing a high-risk patient with cardiovascular comorbidities.